FIRST EXPERIENCE OF USING SUBCUTANEOUS ENDOSCOPIC PLASTIC SURGERY FOR RECTUS ABDOMINIS DIASTASIS AND UMBILICAL HERNIA USING THE SCOLA METHOD - I. V. Makarov; P. D. Stepanov; D. Yu. Stepanov; E. S. Lopukhov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
In this article, we analyzed treatment of patients who had undergone endoscopic subcutaneous plastic surgery using the Scola method for rectus abdominis diastasis and ventral hernias of the anterior abdominal wall. This is a case series which included 4 women. Endoscopic subcutaneous plastic surgery using the Scola method provides an optimal solution for the main tasks in herniology, such as reliable defect repair, good aesthetic results, and perfect cosmetic effect of surgery.